Feeding habits of the fishes Euthynnus lineatus and Scomberomorus sierra (Perciformes: Scombridae) in the Eastern Tropical Pacific - Sandoval Ramírez, Adriana (2020)
ABSTRACT. Introduction: Black skipjack, Euthynnus lineatus, and Pacific sierra, Scomberomorus sierra, are of great economic importance in the small-scale fishery of the Tropical Eastern Pacific and in particular in the study area. Objectives: The objectives of the present study were to assess the diet components of E. lineatus and S. sierra, as well as to evaluate the niche width, trophic level, and trophic overlap between the two species, by size and season. Methods: Biological samples were obtained weekly from small-scale fishery catches in Bahía de Acapulco, Mexico. The E. lineatus sampling period occurred from October 2016 to October 2017, whereas S. sierra was sampled from October 2016 to June 2018. The Prey-specific Index of Relative Importance (% PSIRI) was used to evaluate the importance of each prey item in the diet of the predator. Levin´s index (Bi) was used as a measure of niche width. The Morisita-Horn index was used to evaluate diet overlap by size (juveniles or adults), by season (dry or wet), and between the two species. The trophic level (TL) of predators was calculated using the Cortés´ method. Results: A total of 262 E. lineatus stomachs were analyzed (42 % were empty and 58 % contained food) and a total of 209 S. sierra stomachs were analyzed (74.6 % were empty and 25.3 % contained food). Of the total E. lineatus specimens sampled, 107 were juveniles and 155 were adults. Black skipjack juveniles fed on five food items and adults fed on 13 food items. Of the total S. sierra specimens sampled, 75 were juveniles and 134 were adults. Pacific sierra juveniles and adults fed on five food items. The diet of the two species comprised fish, mollusks, and crustaceans. The two species showed narrow niche width. The diet of juvenile and adult E. lineatus presented differences with growth, contrary to what was observed for juveniles and adults of S. sierra. There were no significant differences in diet by season for both species. The trophic overlap obtained between the two species was low. The trophic level calculated for both species indicated that are tertiary consumers. Conclusions: Black skipjack and Pacific sierra are tertiary predators and present a specialist behavior, feeding mainly on fish from the families Engraulidae and Clupeidae. Although a degree of similarity in the dietary food components of these species was observed, there was not a high degree of interspecific competition for food.